2023
DOI: 10.3390/biomedicines11041131
|View full text |Cite
|
Sign up to set email alerts
|

RAGE Inhibitors in Neurodegenerative Diseases

Abstract: Nonenzymatic reactions of reducing sugars with primary amino groups of amino acids, proteins, and nucleic acids, followed by oxidative degradations would lead to the formation of advanced glycation endproducts (AGEs). The AGEs exert multifactorial effects on cell damage leading to the onset of neurological disorders. The interaction of AGEs with the receptors for advanced glycation endproducts (RAGE) contribute to the activation of intracellular signaling and the expression of the pro-inflammatory transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 104 publications
0
10
0
Order By: Relevance
“…With its documented neuroprotective and antioxidant properties, supplementation with fisetin emerges as a strategic and promising intervention. Fisetin's multifunctional effects on AGEs inhibition, its role in disrupting RAGE-ligand interactions, and its impact on gut microbiota collectively position it as a valuable candidate for preventing neurodegenerative diseases [23]. This aligns with the broader strategy of supplementing dietary polyphenols to modulate the AGEs-RAGE and microbiota-gut-brain axes, presenting a holistic and forward-thinking approach to neuroprotection.…”
Section: Introductionmentioning
confidence: 97%
“…With its documented neuroprotective and antioxidant properties, supplementation with fisetin emerges as a strategic and promising intervention. Fisetin's multifunctional effects on AGEs inhibition, its role in disrupting RAGE-ligand interactions, and its impact on gut microbiota collectively position it as a valuable candidate for preventing neurodegenerative diseases [23]. This aligns with the broader strategy of supplementing dietary polyphenols to modulate the AGEs-RAGE and microbiota-gut-brain axes, presenting a holistic and forward-thinking approach to neuroprotection.…”
Section: Introductionmentioning
confidence: 97%
“…Interestingly, RAGE can also facilitate the transport of Aβ across the blood-brain barrier (BBB) into the brain. Additionally, AGE-RAGE binding triggers the activation of nicotinamide adenine dinucleotide phosphate (NADPH) oxidase, leading to increased production of reactive oxygen species (ROS), malondialdehyde (MDA), and superoxide anion, thus exacerbating oxidative stress and AGE levels ( Reddy et al, 2023 ). Studies have shown that overexpression of proteins in the AGEs/RAGE/NF-κB pathway in the brains of SD rats injected with lipopolysaccharide (LPS) results in elevated levels of IL-1β, IL-6, and TNF-α, alongside increased oxidative stress ( Li et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, HMGB-1 and sRAGE have been described to correlate inversely in the blood circulation of healthy individuals [ 51 ]. As a brain aging hallmark under pathological conditions, reduced levels of sRAGE have been specifically described to be a risk biomarker of neurodegenerative conditions [ 52 ], including mild cognitive impairment, early cognitive decline in type-2 diabetes, AD, and vascular dementia, among others [ 28 , 29 , 30 , 31 , 32 , 53 ]. However, increased sRAGE levels were also described to prevent harmful effects of HMGB1–RAGE interaction as an antioxidant response to the amplification of pathological pro-inflammatory processes and exacerbated oxidative stress conditions [ 31 , 54 ].…”
Section: Discussionmentioning
confidence: 99%